University Social Studies Students’ Knowledge Of The Components Of Environmental Education And Their Participation In Environmental Protection - Dania, P. O; Sunday, Obro (Advances in Social Sciences Research Journal, 2017)
This study investigated University Social Studies students’ knowledge of the components of Environmental Education and their participation in environmental protection. The study outlined the knowledge components of Environmental Education to include verification ability and ability to synthesize environmental issues. A sample of five hundred (500) students was used for the study from universities where social studies education programme exists. The design used for the study was a survey design method. The research used a self-structured instrument tagged ‘Knowledge Component and Participation in Environmental Protection’ Questionnaire (KCPEQ). Two hypotheses were formulated to guide this study and these were analyses using Person Product Moment Correction Analysis (PPMC). It was fund out that students’ verification ability of environmental problems influences their participation in environmental protection. It also revealed that students ability to synthesize environmental Education issues significantly influence their participation in environmental protection. It was on this basis that it was recommended that verification of environmental problems be made internal respect of Environmental Education curricula. Students should be made to make-on-the-spot assessment of degraded environment in their course of study. Also, information gathered from various environmental issues should avail students to participate significantly in environmental protection.